Bringing BIM to archaeological heritage: Interdisciplinary method/strategy and accuracy applied to a megalithic monument of the Copper Age. - Moyano, Juan; Odriozola, Carlos P.; Nieto-Julián, Juan E.; Vargas, Juan M.; Barrera, José A.; León, Javier (Journal of Cultural Heritage, 2020)
• 3D reconstruction of complex shapes in archaeology. • TLS point cloud data is used to build a parametric model in archaeology. • The interdisciplinary approach as a methodology for the construction of A-BIM. • The 3D reconstruction of the assets is performed at millimetre accuracy. Studies on 3D reconstruction have evolved from traditional modelling methods into Building Information Modelling. This technology allows for creating 3D models based on ontologies, including the information of the heritage assets. The inclusion of Terrestrial Laser Scanning data within the BIM models constitutes the Scan-to-BIM approach, which is not yet sufficiently explored for archaeology. Thus, this paper delves into the A-BIM methodology, the application of BIM in archaeology. This is carried out through the case study of a megalithic monument of the Copper Age, called the tholos of La Pastora, in Seville, Spain. The 3D scanning point cloud data is used to create BIM parametric objects with complex archaeological shapes. The results show a difference of ±2.5 mm between the parametric model of the tholos chamber and the measurements obtained using the laser scanner.